A Community Science Approach to Conservation Challenges Posed by Rebounding Marine Mammal Populations: Seal-Fishery Interactions in New England - Bogomolni, Andrea; Nichols, Owen C.; Allen, Dee (Frontiers in Conservation Science, 2021)
Between 1880-1962, gray and harbor seals were targeted in legal seal bounty hunts across Maine and Massachusetts due to a perceived competition with commercial fisheries. Following their extirpation 50 years ago, legislative protections allowed seals to recolonize historical grounds along the New England coast. With this conservation success story, conflict has re-emerged as seen in the numerous media articles reflecting a temperament beckoning to the past century, with calls to cull the population and the spread of misinformation. The return of seals after decades of near-absence has created a new ecological and psychological baseline for New Englanders where for three generations, seals were rarely present. Although seals are statutorily protected species, unlike the tools and resources available for depleted, threatened or endangered species, the support needed to increase opportunities for coexistence of humans with rebounding pinnipeds, are comparatively lacking. Even as gray seals have the highest fisheries bycatch levels of any marine mammal in the U.S., resources to address these management challenges are minimal due to limitations and prioritization processes for committing available support. While seal conservation has been a success, the manner in which management is often separately applied to ecosystem elements (e.g., harvested species, protected species) contributes to knowledge gaps, and a disconnect between the goals of conservation to sustainably utilize natural resources while also protecting the intrinsic value of resources for ecosystem health. Solutions to such coexistence challenges could benefit from a more holistic ecosystem conservation approach. To address these disconnects, a two-day workshop was convened to understand seal-fishery interactions where we provided opportunities for community members to meet and learn from one another including, but not limited to, fishermen, natural resource managers, marine mammal stranding response personnel and scientists. A convening that might otherwise result in tumultuous and adversarial engagement, we used as a tool to engage. This community science approach led to long-term relationships that have allowed for successful applied, and community driven, solutions. Here we share the lessons learned and subsequent partnerships. Our intent is to share our approach to address other marine mammal conservation conflict challenges, allowing for collaborative pathways toward long-term coexistence.